Ambiência infantil em espaços públicos: um estudo entre a Praça e o Parque Estadual Lagoa da Jansen em São Luís, Maranhão. - Mariz, Émile Fróis Rios (2022)
Public spaces should provide a good interaction of all people with the city and offer possibilities to experience leisure and displacements facilitated as equal opportunities. Planning and designing public spaces with appropriate children ambience, besides favoring the development of children, can raise the quality of life of people, encourage a society more attentive to urban issues, confer citizenship, awaken sense of collectivity and sense of belonging, inclusion, welcome and neighborhood. In this sense, this Course Conclusion Work deals with a theme focused on public spaces and children's leisure, and has as its objective the study of children's ambience in an urban section that involves the Praça da Lagoa da Jansen, the Praça do Foguete and part of the Lagoa da Jansen Park in the city of São Luís, Maranhão. As a way of elaboration and initial conduction for the development of the work, there is the elaboration of a theoretical framework that addresses concepts of public spaces and ambience, as well as issues such as universal design, accessibility and children's leisure. In order to complement the support for the study, we also present principles as recommendations for the planning and design of urban spaces for children, and project references as examples of public spaces prepared and qualified for children's leisure. As results, we have a reading of the object of study confronted with the recommendations of the authors studied and also a general approach to identify the most significant public spaces for children's leisure in the city of São Luís.